Pharmacognostic Evaluation of Maesobotrya barteri (Baill) Hutch and Maesobotrya dusenii Pax (Euphorbiaceae) Leaves - Suleiman Mikailu*; Oko-Orji Onyekachi Kalu (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Pharmacognostic evaluations have paved the way for compilation of African Pharmacopeia. This study reports the pharmacognostic profile of Maesobotrya dusenii (Pax) Pax and Maesobotrya barteri (Baill.) Hutch. Method: The two plants were collected from the Etche Area of Rivers State. Macroscopic and microscopic evaluations of the stomata number and palisade numbers were done. Phytochemical screening was conducted using standard methods and physicochemical parameters were evaluated to determine moisture content, extractive values and ash content. The flavonoid content of M. barteri was also evaluated using quercetin equivalent. Results: Maesobotrya dusenii revealed anomocytic type of stomata while M. barteri showed a mixed type of stomata involving anomocytic and anisocytic. Phytochemical screening revealed the presence of triterpenoids, saponins and carbohydrates in M. dusenii, while in M. barteri flavonoid, cardiac glycosides, saponin, triterpenoids and alkaloids were present. Maesobotrya dusenii and M. barteri showed the highest extractive value by chloroform. Conclusion: The study revealed distinctive features between M. dusenii and M. barteri that can be used in their identification, authentication and preparation of monograph for the plants.